فتوی نویسی :اہمیت و معنویت اور تاریخ و ارتقاFatwa Writing: Significance, History and Evolution (Al-Qamar, 2020)
A fatwa is a non-binding legal opinion on a point of Islamic law (Sharīʻah) given by a qualified Jurist (Muftī) in response to a question established by a private individual, judge or government. Issuing fatwas is called Iftāʻ. This paper explores the significance, history and evolution of issuing a Fatwa. It finds that Iftāʻ and fatwa is an exclusive Muslim intellectual tradition that provides Sharīʻah based solutions for the problems having no clear solution in Quran, Ḥadīth and sayings of the pious companions of the Holy Prophet (ﷺ). In this age of globalization, knowledge and research, utility of Fatwa and its need has been increased even more than ever before.
Keywords: Fatwa; significance; history; evolution